Trade Creation and Trade Diversion in the Council of Mutual Economic Assistance: 1954-1970 - Pelzman, Joseph (American Economic Review, 1977)
The Council of Mutual Economic Assistance' (CMEA) has been in existence since January 1, 1949. Despite the fact that its creation2 was attributed to the establishment of the Organization for European Economic Cooperation (OEEC), its declared ultimate goal was the promotion of a process of integration among the East European countries.3 For the Soviet Union, economic integration is primarily a means of increasing its political and economic control over the other CMEA member states. On the other hand, for the more developed members of CMEA, economic integration is a natural outgrowth of their desire to industrialize and maximize the economic gains from trade and cooperation.4 Beginning in the early 1960's, the shift from an extensive to an intensive growth policy in response to the decline in growth rates created a drive towards economic integration within CMEA. The desire to increase the static gains from international trade was further prompted by its expected contribution to rapid industrialization and efficiency. This shift to intensive growth combined with the desire for rapid industrialization has also meant greater decentralization of economic decision making and the use of limited market mechanisms.5 The CMEA as it exists today differs from the EEC customs union in one major respect. It does not rely a clearly defined common external tariff. A proxy of such a tariff, however, originates in the annual bilateral negotiations between the CMEA member states. Consequently, it is quite possible to find the existence of trade creation and/or diversion as effects of economic integration within CMEA. The analysis of trade creation and/or diversion in this study is of an ex post type. The model utilized to determine these effects is a cross-sectional trade-flow model of the type developed by Jan Tinbergen, Pentti Poyhonen, Kyosti Pulliainen, and Hans Linnemann. Using this cross-sectional trade-flow equation to empirically test the integration effects of CMEA we initially pool the cross-sectional and time-series data for both aggregate and disaggregate trade flows. In the case of disaggregate commodities, because we cannot rule out the possibility that the regression disturbances in different equations are mutually correlated, we use the estimating procedure de*Assistant professor of economics, University of South Carolina. I am grateful to the managing editor of the Review and an anonymous referee for their helpful comments an earlier draft of this paper. Responsibility for any errors is solely mine. Substantial portions of this article were previously published in the ACES Bulletin, Vol. XVIII, No. 3, Fall 1976, and this material appears here with the permission of the Association for Comparative Economic Studies. Discussion of the article and a reply appear in the same journal, Spring 1977. IThe CMEA member countries are: Bulgaria, Czechoslovakia, East Germany, Hungary, Poland, Romania, and the USSR. 2The most plausible reasons for CMEA's origin are presented in Michael Kaser, chs. 1, 2, and in I. T. Berend, pp. 15 17. 3The communique published January 22, 1949 declared that the CMEA was created on the basis of equal representation and with the task of exchanging economic experience, technical aid and rendering mutual assistance with respect to raw materials, foodstufTs, machines, equipment, etc.. .' Heinz Kohler (pp. 377 95). Economic integration is detined as a process aimed at reducing the disparity between scarcities in the various C'MEA countries by eliminating obstacles to trade. 4See the author ( 1976a, ch. 3). 5 For a further discussion of the links between international trade, industrialization, and the reflbrms, see the author (1976a, ch. 2).